EVOLUTION OF THE FORMATION OF IDEAS ABOUT DEATH IN PHILOSOPHY (TAMADDUN NURI JURNALI, 2024)
The article shows the history of the formation of views on death in the history of philosophy. Not only a psychological approach to death, but also philosophical and religious approaches are given.